Ionogel Electrolytes through Sol-Gel Processing. - Horowitz, Ariel. (2017)
Abstract: Electrical energy needs have intensified due to the ubiquity of personal electronics, the decarbonization of energy services through electrification, and the use of intermittent renewable energy sources. Despite developments in mechanical and thermal methods, electrochemical technologies are the most convenient and effective means of storing electrical energy. These technologies include both electrochemical cells, commonly called batteries, and electrochemical double-layer capacitors, or "supercapacitors", which store energy electrostatically. Both device types require an ion-conducting electrolyte. Current devices use solutions of complex salts in organic solvents, leading to both toxicity and flammability concerns. These drawbacks can be avoided by replacing conventional electrolytes with room-temperature molten salts, known as ionic liquids (ILs). ILs are non-volatile, non-flammable, and offer high conductivity and good electrochemical stability. Device mass can be reduced by combining ILs with a solid scaffold material to form an "ionogel," further improving performance metrics. In this work, sol-gel chemistry is explored as a means of forming ionogel electrolytes. Sol-gel chemistry is a solution-based, industrially-relevant, well-studied technique by which solids such as silica can be formed in situ. Previous works used a simple acid-catalyzed sol-gel reaction to create brittle, glassy ionogels. Here, both the range of products that can be accomplished through sol-gel processing and the understanding of interactions between ILs and the sol-gel reaction network are greatly expanded. This work introduces novel ionogel materials, including soft and compliant silica-supported ionogels and PDMS-supported ionogels. The impacts of the reactive formulation, IL identity, and casting time are detailed. It is demonstrated that variations in formulation can lead to rapid gelation and open pore structures in the silica scaffold or slow gelation and more dense silica morphologies. The IL identity is shown to have an impact on the apparent strength of the acid catalyst, leading to significant shifts in gelation time. Delayed casting is proven to be an optimal technique for avoiding pore blockage when combining ionogels with high surface area electrodes for supercapacitor applications. Finally, a simple recycling process is proposed, establishing that ILs can be easily reclaimed from silica-supported ionogels and reused, thereby validating the reputation of ILs as "green" materials.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Matthew Panzer.; Committee: William Moomaw, David Ofer, and Daniel Ryder.; Keywords: Chemical engineering, Materials Science, and Energy.